DETERMINASI MANAJEMEN KEUANGAN PRIBADI MAHASISWA - Prihatingsih, Prihatiningsih (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2021)
This study aims to find out and analyze the factors that affect students' financial management ability. A sample of 100 students from Politeknik Negeri Semarang, Universitas Diponegoro dan Universitas Negeri Semarang with multiple Linear regression analysis tools after passing the validity test, reliability test and classic assumption test. Based on statistical test results obtained, financial education variables, financial literacy, academic ability, and work experience have a positive and significant effect on student personal financial management variables.